2011
DOI: 10.1179/1743132811y.0000000006
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of carmustine wafers for older patients with glioblastoma multiforme: prolonging survival

Abstract: Objective Peak incidence of glioblastoma multiforme (GBM) occurs in individuals aged 65 years and older. The goal was to evaluate the efficacy of carmustine wafers in prolonging survival for older GBM patients. Methods One hundred and thirty-three consecutive patients aged 65 years and older who underwent surgery for an intracranial primary (de novo) GBM from 1997–2007 were retrospectively reviewed. Among these 133 patients, 45 patients with carmustine wafer implantation were matched with 45 patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…The multivariate proportional hazards regression analysis was used to identify an association between resection number and survival. This analysis was conducted after controlling for preoperative (age, KPS score, and periventricular tumor location), 4,8,22,23 intraoperative (extent of resection), 6,20,22,25,31 and postoperative factors (carmustine wafer implantation, 3,9,27,36 temozolomide chemotherapy, 16,34 and radiation therapy 14 ) known to be associated with survival. In addition, to evaluate the role of resection number and survival, a case-control study was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The multivariate proportional hazards regression analysis was used to identify an association between resection number and survival. This analysis was conducted after controlling for preoperative (age, KPS score, and periventricular tumor location), 4,8,22,23 intraoperative (extent of resection), 6,20,22,25,31 and postoperative factors (carmustine wafer implantation, 3,9,27,36 temozolomide chemotherapy, 16,34 and radiation therapy 14 ) known to be associated with survival. In addition, to evaluate the role of resection number and survival, a case-control study was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Second, formal volumetric analysis using manual tumor tracing was performed using manual segmentation with region of interest analysis to measure tumor volume (in cm 3 ) on the basis of contrast enhancement, as previously described. 5,20 …”
Section: Extent Of Resection Analysismentioning
confidence: 99%
“…These drugs are being used as second-line therapeutics for malignant brain tumors, notably glioblastoma multiforme, metastizing melanoma, Hodgkin lymphoma and brain metastases of different origin. [2][3][4][5][6][7][8][9] The main molecular target of these agents is the DNA inducing, upon generation of nucleophilic chloroethylenium ions, a broad spectrum of DNA adducts. 10 From these adducts, it has been suggested that O 6 -chloroethylguanine is the main killing lesion.…”
Section: Introductionmentioning
confidence: 99%